Gender in Power: Breaking Boundaries on Little Mix's "Power" - Simamora, Debora Anriyani; Galaska, Candrika; Maria, Jessicca; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2025)
This study uses Sara Mills' feminist stylistics theoretical framework to analyze how Little Mix's song “Power” actively challenges traditional gender norms through language.  The main goal is to examine how this song challenge gender stereotypes by portraying women as strong and in charge rather than just calling for equality or opposing oppression. Using a descriptive qualitative approach, this study examines song lyrics at three levels: words, phrases/sentences, and discourse in accordance with Sara Mills' theoretical framework (1995). The findings of this study prove that Little Mix's power song is full of lyrics that actively break traditional gender stereotypes, affirming that women can hold and have control, not as a concession from men, but as an inherent right. The language used in the song successfully challenges patriarchal roles, reinforcing the idea that power is not only limited to masculine men but is also accessible to women. The song is a true feminist anthem.